(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2025)
Law is undergoing a deep transformation. The climate crisis and the cultural innovation demand a shift from the anthropocentric paradigm, leading to the recognition of new legal subjects such as animals and ecosystems. These issues are increasingly shaping legislation and call for an active role from legal scholars, both in theory and practice. Through comparative analysis of different legal systems, a unified path is proposed to protect these emerging legal spheres. The jurist becomes a bridge between philosophical reflection and legislative action, contributing to a future founded on cooperation, equity, and sustainability.